Establishing best practices in the use of an upgraded airborne teaching laboratory [data] - Daniels, Steven; Gratton, Guy; Braithwaite, Graham (Cranfield University, 2024)
Qualitative and Quantitative date used to inform the paper "Establishing best practices in the use of an upgraded airborne teaching laboratory"
Keywords: Training Effectiveness'; 'Specialist Airborne Instruction'; 'Practical Aero-engineering'; 'Air Experience'; 'Education'